Resurrection as anti-imperial gospel : 1 Thessalonians 1:9b-10 in context - Pillar, Edward (Minneapolis: Fortress press, 2013)
"Presuming that the heart of Paul's gospel announcement was the news that God had raised Jesus from the dead (as indicated in 1 Thessalonians 1:9b-10), Edward Pillar explores Paul's letter and aspects of the Roman imperial culture in Thessalonica in order to imagine what proclamation would have evoked for its first hearers. He argues that the gospel of resurrection would have been heard as fundamentally anti-imperial. Jesus of Nazareth was executed by means of imperial power, yet the resurrection subverts and usurps the empire's power."--Page 4 of cover.
"Whom he raised from the dead" -- Turning to God -- Turning to God from idols -- "To serve..." -- "The living and true God" -- Waiting... -- "The son from the heavens" -- "Jesus, who rescues us from wrath" -- Conclusion.
Revision of the author's thesis (Ph.D.) -- Trinity Saint David School of Theology, University of Wales, 2012.
Includes bibliographical references (pages 267-294) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Commentaries; Resurrection; Christianity and culture -- Rome -- History -- Early church, ca. 30-600.